Introverted Learners Problems and Solving Strategies in Speaking English - Hanifa, Nur; Anita, Anita; Suaidi, Afif (English Education: Jurnal Tadris Bahasa Inggris, 2022)
This study investigated the problems and strategies for solving introverted learners' problems in speaking English. Qualitative research design was used in this research. An online MBTI test was used to recruit introverted participants. This research involved eight students at the fourth semester of the English Education Department of UIN SMH Banten. The researchers gathered the data through an online personality test, questionnaire, and interview. The result of this research showed that there were three problems introvert learners facing when they spoke English: linguistic problems (pronunciation, grammar, and vocabulary), feeling shy or nervous, and lack of self-confidence. This study also discovered that there were three factors affecting their problems: affective, environment, and personality. This research found six strategies to solve introverted learners' problems in speaking English. The strategies were as such; selfpractice as much as possible, regulating the breath, learning through social media platforms, taking a note of unfamiliar words, listening to English songs, and playing online games.